Positive Behavioural Support as an alternative to medication. Issue 1 (28th December 2018) - Lee, Ruth M.; Rhodes, Jennifer A.; Gerrard, David
Abstract : Purpose: The purpose of this paper is to demonstrate how Positive Behavioural Support (PBS) can be used as an alternative to psychotropic medication to improve the quality of life of an individual with a learning disability and behaviour described as challenging. Design/methodology/approach: A single case design was utilised. A unique PBS stopping over medication of people with a learning disability, autism or both (STOMP) clinic model was developed and PBS was used in line with National Institute for Health and Care Excellence (NICE) guidance. This included functional behavioural assessment, to support understanding of the reasons behind behaviour described as challenging, and a gradual medication reduction. Findings: This case study found that antipsychotic medication used to manage behaviour that challenges could be safely reduced and individual quality of life increased when PBS was used as an alternative. Originality/value: STOMP is a project supported by NHS England aimed at reducing the inappropriate prescribing of psychotropic medication to manage behaviour that challenges. NICE guidance recommends that behaviour should be more appropriately understood through PBS. More research is needed to demonstrate how the two work together for safe medication reduction and improved quality of life.